Managerial Ties, Market Orientation, and Export Performance: Chinese Firms Experience–ADDENDUM. (7th August 2017) - Yan, Hui; He, Xinming; Cheng, Binwu
Abstract : In this addendum we provide further information on our results and findings as well as explanations and suggestions in relation to the low R 2 .Table 1 provides additional information i.e., the standard error of all estimates, exact p values instead of asterisks as the significance level on the base of Table 3 in the published manuscript.